BINCANG SEHAT SEBAGAI UPAYA PENCEGAHAN SEKS BEBAS DIKALANGAN REMAJA (FREE SEKS BUKAN TIPE KU : AKU CEGAH AKU AMAN) - Nelyta Oktavianisya; Yulia Wardita; Laylatul Hasanah; Sugesti Aliftitah (Jurnal Pengabdian kepada Masyarakat, 2025)
Free sex behavior is one of the serious problems faced by teenagers in Indonesia, which is caused by various factors such as lack of knowledge about reproductive health, the influence of socializing, and technological advances that facilitate access to sexual information. Based on the results of an initial survey of students at SMAN 1 Batuan, it was found that 60% of them did not fully understand the dangers, factors, impacts, and prevention of free sex. For this reason, Community Service activities were carried out through the "Health Talk Show" program with the theme Free Sex Is Not My Type as an effort to increase students' knowledge and awareness of free sex. The method of implementing the activity includes coordination, compiling educational materials, implementing health discussion with a two-way communication approach, and forming adolescent squad as extension agents. The results of the activity showed an increase in participant knowledge, from 63% in the less category to 66% in the good category after the program was implemented. These findings reinforce the importance of comprehensive sex education, family support, and ongoing guidance from various parties in shaping the character of responsible adolescents. This activity shows that an interactive educational approach based on local cultural values is effective in preventing risky sexual behavior among adolescents.